INVENTARISASI TUMBUHAN OBAT DI DESA SILAPING KECAMATAN RANAH BATAHAN KABUPATEN PASAMAN BARAT - Gena, Hobi - (STKIP PGRI Sumbar, 2014)
Plant in Indonesia is very diverse and most can be used as medicinal plants. The plant iswidespread in Indonesia ranging from urban to rural areas, one of which is in the village Silaping.People in this village still use plants as medicine, by reason of drugs from plants traditionallyprocessed cheaper and some communities also have the expertise to cultivate it themselves. Thisstudy aims to determine the types of medicinal herbs in the village Silaping Batahan PasamanDistrict of West Domains. The study was conducted in January-March 2014. The method used isdescriptive method with observation and interview techniques. The results showed that 103 speciesof medicinal plants consisting of 52 species and most numerous species in the Asteraceae andZingiberaceae familia.